Uma proposta de metodologia para an?lise de desempenho de redes IEEE 802.11 combinando a ger?ncia SNMP e ferramentas de simula??o - Ieno J?nior, Eg?dio (2003)
The importance of computer network management becomes increasingly unanswerable. With the increase of these networks in complexity and size, a good knowledge about the possible management tools available for data collection is essential. This data will be responsible for informing the network administrator of your current situation. SNMP is a protocol capable of collecting information in a management information base (MIB) and making it available in a management station to be handled and analyzed. One of the possible analyzes that can be done with the data collected is related to the performance of the network, through the objects responsible for these indicators. In this dissertation, a methodology for Network Performance Analysis is proposed, combining SNMP Management in a growing network standard, which is IEEE 802.11, and the simulation process. Also in this methodology is presented a case study illustrating the possibility of Capacity Planning in a network that has its main backbone extended with wireless networks.